X-ray phase-contrast 3D virtual histology characterises complex tissue architecture in colorectal cancer - Svetlove, Angelika; Griebel, Titus; Albers, Jonas; D’Amico, Lorenzo; Nolte, Philipp; Tromba, Giuliana; Bohnenberger, Hanibal; Alves, Frauke; Dullin, Christian (Frontiers in Gastroenterology, 2023)
Precise morphological analysis of tumour tissue samples is crucial for accurate diagnosis and staging of colorectal cancer (CRC), but remains limited by the 2D nature of conventional histology. Our aim is to offer a 3D representation of tissue samples by means of X-ray-based imaging to facilitate the evaluation of clinically relevant features in cancer tissue, a process that is currently subject to various restrictions. In this study, we show that propagation-based synchrotron radiation-based free propagation phase-contrast microcomputed tomography (SRµCT) is suitable for the generation of 3D tumour volumes with 2-µm voxel size using standard formalin-fixed, paraffin-embedded tissue from CRC patients and provides sufficient contrast for virtual histology. We demonstrate that, using an existing registration pipeline, a 2D histologic haematoxylin–eosin slice can be placed in the context of the 3D µCT volume. The precisely registered histologic section can then be used as a “seed point” for the segmentation and depiction of major histologic features. This approach allows for a more comprehensive understanding of the organisation of the tumour in space with respect to other structures such as vessels, fat, and lymph nodes, and has the potential to improve patients’ prognostic outcomes.